Successful treatment with alectinib after crizotinib-induced interstitial lung disease. Issue 3 (December 2015) - Chino, Haruka; Sekine, Akimasa; Kitamura, Hideya; Kato, Terufumi; Ogura, Takashi
Highlights: The patient developed crizotinib-induced interstitial lung disease. The life-threatening disease-flare occurred after cessation of crizotinib. Alectinib could be effectively used without recurrence of interstitial lung disease. Abstract: We herein report a case of a 46-year-old woman with anaplastic lymphoma kinase (ALK)-rearranged stage IV lung adenocarcinoma who received the ALK inhibitor crizotinib as second-line therapy. On the 47th day following crizotinib initiation, a chest computed tomography scan revealed ground-glass opacities with a clinical manifestation of desaturation, although a partial response to treatment was detected. The diagnosis of crizotinib-induced interstitial lung disease (ILD) was confirmed, and crizotinib was discontinued, followed by the initiation of corticosteroid therapy. After improvement of ILD with corticosteroid therapy, alectinib was administered as salvage therapy, resulting in tumor shrinkage without any recurrence of ILD. To the best of our knowledge, this is the first report of successful alectinib treatment following crizotinib-induced ILD. Our results indicate that alectinib could be a promising alternative treatment option in patients with crizotinib-induced ILD.